Detection and Quantification of the E6 Oncogene in Bovine Papillomavirus Types 2 and 13 From Urinary Bladder Lesions of Cattle - Alcântara, Brígida Kussumoto de; Lunardi, Michele; Agnol, Alais Maria Dall; Alfieri, Alice Fernandes; Alfieri, Amauri Alcindo (Frontiers in Veterinary Science, 2021)
Bovine papillomavirus types 2 and 13 can induce tumors in both the cutaneous and mucosal epithelia of cattle. These viral types are associated with the development of benign cutaneous papillomas and malignant lesions in the urinary bladders of cattle, with the latter being known as bovine enzootic hematuria. Among the viral oncoproteins encoded by Deltapapillomavirus DNA, the E6 oncoprotein has an important role in cell proliferation and might be related to cancer initiation and promotion. The aim of this study was to present a standardized SYBR Green-based quantitative PCR for detection and quantification of the bovine papillomavirus 2 and 13 E6 oncogenes in urinary bladder samples from cattle. Twenty-four urinary bladders from cattle displaying tumors (n=12) and normal bladder mucosa (n=12) were tested by quantitative PCR. Of the 12 urinary bladders with tumors, six presented bovine papillomavirus 2 DNA concentrations ranging from 1.05 x 104 to 9.53 x 103 copies/µL, while two had bovine papillomavirus 13 DNA amplified at concentrations of 1.30 x 104 to 1.23 x 104 copies/µL. The healthy bladder mucosa samples were negative for both bovine papillomaviruses. Once the results were confirmed by conventional PCR and direct sequencing, the quantitative PCR assay developed in this study was shown to be a sensitive and specific tool for detecting and quantifying the E6 ORF of bovine papillomavirus 2 and 13 in a variety of clinical samples. Our findings of identification of bovine papillomavirus 2 and 13 DNA in urothelial tumors from cattle suffering from bovine enzootic hematuria agree with data from previous studies, representing the first detection of bovine papillomavirus 13 DNA in malignant bladder lesions of cattle from Brazil.